2000
DOI: 10.1074/jbc.c000099200
|View full text |Cite
|
Sign up to set email alerts
|

Activation of the Cytoplasmic c-Abl Tyrosine Kinase by Reactive Oxygen Species

Abstract: The ubiquitously expressed c-Abl protein tyrosine kinase localizes to both the nucleus and cytoplasm. The nuclear form of c-Abl is activated in the cellular response to genotoxic stress. Here we show that cytoplasmic c-Abl is activated by oxidative stress. The results also demonstrate that mitochondrial cytochrome c is released in the cellular response to H 2 O 2 and that this effect is mediated by a c-Abl-dependent mechanism. In concert with these results, we show that H 2 O 2 -induced apoptosis is attenuated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
143
1

Year Published

2002
2002
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(158 citation statements)
references
References 34 publications
14
143
1
Order By: Relevance
“…More recently, it has been reported that c-Abl activation induces the phosphorylation of Crk in the cytoplasmic compartment (Holcomb et al, 2006). H 2 O 2 is known to selectively activate cytoplasmic, but not nuclear Abl (Sun et al, 2000). Our results suggested that cytoplasmic Abl is responsible for phosphorylation of C3G and induction of apoptotic changes.…”
Section: C3g Is a Target And Effector Of C-abl Functionsupporting
confidence: 61%
See 1 more Smart Citation
“…More recently, it has been reported that c-Abl activation induces the phosphorylation of Crk in the cytoplasmic compartment (Holcomb et al, 2006). H 2 O 2 is known to selectively activate cytoplasmic, but not nuclear Abl (Sun et al, 2000). Our results suggested that cytoplasmic Abl is responsible for phosphorylation of C3G and induction of apoptotic changes.…”
Section: C3g Is a Target And Effector Of C-abl Functionsupporting
confidence: 61%
“…Inhibition of Rap1 activation in c-Abl-expressing cells by co-expression of GFPRap1GAP resulted in reduced apoptosis (Figure 8f). H 2 O 2 induces cell death dependent on c-Abl (Sun et al, 2000). Expression of WT C3G resulted in a significant increase in H 2 O 2 -induced apoptosis, but Y504F mutant, which inhibits signalling dependent on Y504 phosphorylation, reduced apoptosis by 59% (Figures 8g and h).…”
Section: C-abl-mediated Apoptosis Is Dependent On C3gmentioning
confidence: 95%
“…This, and the fact that nuclear p73 tyrosine phosphorylation was similar in viable and apoptotic cells, indicates that cytoplasmic and not nuclear Abl is responsible for serum deprivation-induced apoptosis (Yuan et al, 1997;Agami et al, 1999;Gong et al, 1999;Yuan et al, 1999). In support of these findings, treatment of Cos 7 and A/ A þ / þ cells with H 2 O 2 , which selectively activates cytoplasmic and not nuclear Abl activity (Sun et al, 2000), induced strong Crk phosphorylation and cell death (Figure 6a, b). In contrast, treatment of A/AÀ/À cells with H 2 O 2 failed to induce these responses (Figure 6c).…”
Section: Cytoplasmic But Not Nuclear Abl Phosphorylates Crk In Apopsupporting
confidence: 54%
“…13 In contrast, the association of Gal3 with c-Abl and Arg is readily displayed, and strong tyrosine phosphorylation was also observed under steady-state conditions. These findings are relevant to physiological functions.…”
Section: Discussionmentioning
confidence: 97%